Implementação do SUAS : um estudo sobre as particularidades de Juiz de Fora/MG - Toledo, Sabrina Navarro (2010)
This academic work presents a study of the implementation process of the SUAS - Sistema Único de Assistência Social (Unified System of Social Services) in the city of Juiz de Fora, Minas Gerais, Brazil. It aims to create a draft of the social service politics locally and nationally, to point the direction of the institutionalization of social services in Brazil and in Juiz de Fora and, above all, to highlight the elements which have contributed to the implementation of SUAS in the city, identifying the challenges to the consolidation of the social services policy as lawful policies and a duty of the State. The research done had as its analysis axis the organizational and institutional characteristics of social services politics in Juiz de Fora, pointing to the uses and concepts of said politics nationwide.